Three new species of Chromatonotus Hebard, 1920 and new combination for Chromatonotus elegantula R.S. Albuquerque, 1974 (Blattaria: Ectobiidae) - Lopes, Sonia Maria; de Oliveira, Edivar Heeren (Zootaxa, 2019)
Three new species of Chromatonotus Hebard (C. bahiaensis, C. dextrodigitatus, C. diminutivus) are described from Mato Grosso, Bahia and Pernambuco states, Brazil, and Chromatonotus elegantula R.S. Albuquerque, 1974 is transferred to Ischnoptera Burmeister, 1838 as I. elegantula (R.S. Albuquerque, 1974) comb. nov. The material studied in this paper were stored in the Entomological Collection of Department of the Entomology, Museu Nacional, but was lost in the fire that took place in the Museu Nacional on September 2, 2018.